Nationality and statelessness under international law - Edwards,Alice,Ed (Cambridge, 2014)
"Written by leading experts, Nationality and Statelessness under International Law introduces the study and practice of 'international statelessness law' and explains the complex relationship between the international law on nationality and the phenomenon of statelessness. It also identifies the rights of stateless people, outlines the major legal obstacles preventing the eradication of statelessness and charts a course for this new and rapidly changing field of study"--